MANAGERIAL STRENGTHENING OF KEMBAR JAYA SEAFOOD TOWARDS AN INDEPENDENT PROCESSING AND MARKETING GROUP (KELOMPOK PENGOLAH DAN PEMASAR/POKLAHSAR) - Anthon Efani; Moh Khusaini; Asfi Manzilati (Caring : Jurnal Pengabdian Masyarakat, 2022)
The most prominent potential in the Bajulmati area is the potential for capture fisheries. Even so, the Bajulmati area also has the potential for processed fishery products, but the potential for these processed products does not yet have optimal marketing. This is due to the lack of marketing and business management systems that are owned. The purpose of this service activity includes: (1) Integrating the performance of Higher Education (Universitas Brawijaya), with processing and marketing group (kelompok pengolah dan pemasar/POKLAHSAR) Kembar Jaya Seafood in Bajul Mati, Malang Regency to improve business sustainability POKLAHSAR Kembar Jaya Seafood, (2) Creating business sustainability through business management training, (3) Increasing hard skills in managing financial flows through financial management training, (4) Increasing the competitiveness of POKLAHSAR Kembar Jaya Seafood products through product branding, (5) Increasing standardization of fish processing products at POKLAHSAR Kembar Jaya Seafood, Malang Regency both in terms of hygiene, halal, and packaging, (6) Creating a marketing and sales system so that fish processing businesses at POKLAHSAR Kembar Jaya Seafood are able to carry out marketing and sales effectively , (7) increasing the role of Brawij University I am in developing the area around the campus by involving students. This community service activity is carried out using managerial assistance methods including business management training, financial management, product branding socialization, product standardization assistance, initiation of effective marketing and sales systems for souvenir needs. This service program is able to make POKLAHSAR Kembar Jaya Seafood a sustainable business. Sustainability in question is not only productivity sustainability but also sustainability as a center for processed fishery products. The five programs proposed as solutions ranging from business management training, financial management, product branding training, product standardization assistance and the creation of an effective marketing and sales system went well accompanied by enthusiasm from POKLAHSAR Kembar Jaya Seafood.